Evaluation of serum insulin-like growth factor 1 and its significance in thyroid cancer: An observational study. Issue 21 (28th May 2021) - Hou, Yu-Lei; Chen, Juan-Juan; Zhang, Xiang; Chen, Hui
Abstract : Abstract: Serum insulin-like growth factor 1 (IGF-1) is elevated in different cancers. However, relationships between serum IGF-1 and thyroid cancer (TC) are scarce. The present study aimed to investigate the clinical significance of serum IGF-1 in TC. Serum was collected from 124 TC patients, 50 patients with benign nodules, and 50 healthy controls. Serum IGF-1 levels were measured and compared. Relationships were investigated between IGF-1 and clinical characteristics. A receiver operating characteristic (ROC) curve was plotted to explore the diagnostic value of IGF-1 in TC. Serum IGF-1 levels were significantly higher in TC than that of healthy controls and benign nodules ( P = .003; P < .001). Serum IGF-1 levels were higher in TC patients with advanced stage than early stage ( P = .029). Higher serum IGF-1 levels were found in patients with lymph node metastasis present and (tumor size >1 cm) than that of patients without lymph node metastasis ( P = .018) and (tumor size ⩽1 cm) ( P = .031). Serum IGF-1 levels were higher in patients with a solitary nodule than multinodular nodules ( P = .043). The serum IGF-1 cutoff value for a TC diagnosis was 216 ng/mL with a sensitivity of 53.2%, a specificity of 74.0%, a positive predictive value (PPV) of 83.5%, and an area under the curve was of 0.71. Serum IGF-1 was significantly correlated with tumor stage, size, and lymph node metastasis. Serum IGF-1 shows great potential as a laboratory marker for TC.